(untitled) (Global Journals of Research in Engineering, 2012)
This paper presents and analyzes a new biogas based catalytic reforming-processing system for the conversion of gaseous hydrocarbons (coming from manure type anaerobic digesters) such as methane into hydrogen and carbon oxide mixtures. The exit synthesis gas (syn-gas) is introduced to power effectively high temperature fuel cells such as SOFC types for combined efficient electricity generation. Moreover, this research targets on the description and design aspects of permreactors (permeable reformers) carrying the same type of renewable-biogas reforming reactions. The goals of such a research include turnkey system and process development for the biogas based power generation and fuel cell industries. The proper utilization of biogas and waste type resources (coming from manure type anaerobic digesters) for green-type/renewable power generation with increased processing capacity and efficiency via SOFCs is introduced as well. Pollution reduction is under additional design benefit in the described catalytic processors-fuel cell systems, at the same time. Three different reactor configurations are examined and compared. The use of a membrane reformer and of a catalytic membrane reformer offer better hydrogen and syngas yields and methane conversions than the corresponding non-membrane plug flow reactor.